1994
DOI: 10.1093/oxfordjournals.humrep.a138444
|View full text |Cite
|
Sign up to set email alerts
|

Genetics: Disturbances of nuclear condensation in human spermatozoa: search for mutations in the genes for protamine 1, protamine 2 and transition protein 1

Abstract: During spermiogenesis, the successive replacement of the somatic histones by basic proteins, the transition proteins and protamines, allows normal sperm nuclear condensation. It was suggested that disturbances in nuclear condensation may result in male infertility. Here we report the first molecular analysis of the structure of three genes which code for germ cell-specific nuclear proteins, namely protamine 1 (PRM1), protamine 2 (PRM2) and transition protein 1 (TNP1) in infertile men with disturbed sperm chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…Indeed, many investigators have attempted to identify any significant mutations in the protamine coding regions [de Yebra and Oliva 1993;Schlicker et al 1994;Aoki et al 2006a]. However, Tanaka, et al in 2003 identified one azoospermic patient with a premature stop codon in P2 [Tanaka et al 2003].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many investigators have attempted to identify any significant mutations in the protamine coding regions [de Yebra and Oliva 1993;Schlicker et al 1994;Aoki et al 2006a]. However, Tanaka, et al in 2003 identified one azoospermic patient with a premature stop codon in P2 [Tanaka et al 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups evaluated the coding sequences of protamine 1, 2 and transition protein 1, 2 to identify specifically relevant alterations that may possibly explain the cause of protamine deregulation [de Yebra and Oliva 1993;Schlicker et al 1994;Tanaka et al 2003;Miyagawa et al 2005;Aoki et al 2006a;Iguchi et al 2006]. Generally, there was no correlation between the absence of protamines and mutations within the coding regions of the protamine genes or transition protein genes.…”
Section: Introductionmentioning
confidence: 99%
“…A fertile man with an influenza-induced fever (39.9ЊC; Figure 2) also expressed an unprocessed P2 precursor coincident with an increased histone:protamine ratio, decreased free -sulfhydryl groups, and increased DNA stainability . The presence of an unprocessed P2 precursor (de Yebra et al, 1998) combined with evidence that genes encoding P1, P2, and transition proteins are normal (Schlicker et al, 1994) indicates that incomplete protein processing of P2 can lead to chromatin abnormalities. The role of abnormal P2 in infertility is substantiated by the importance of P2 in the formation of zinc-finger structures (Bianchi et al, 1994) and intermolecular and intramolecular disulfide bonds, which are necessary for chromatin stabilization (Calvin and Bedford, 1971;Bedford and Calvin, 1974;Evenson et al, 1980b).…”
Section: Sources Of Sperm Chromatin Abnormalitiesmentioning
confidence: 99%
“…Sperm head morphology has been established by the World Health Organization (WHO) as the most important criterion to assess the fertility of males. There is, however, evidence and growing concern that not all sperm with normal shape are fully functional and may contain DNA that is improperly packaged [15][16][17]. Fertilization events involving abnormal sperm could have adverse effects on early embryo development or lead to genetic disease.…”
Section: Biophotonicsmentioning
confidence: 99%